Privacy-Aware Image Authentication from Cryptographic Primitives. (2nd November 2020) - Chen, Haixia; Huang, Xinyi; Wu, Wei; Mu, Yi
Abstract: Image authentication is the process of verifying image origin, integrity and authenticity. In many situations, image authentication should allow reasonable image editing, which does not introduce any wrong information against the original one. While it has been studied both extensively and intensively with considerable efforts, there is no satisfactory method supporting region extraction. This paper presents a solution to address the issue of privacy protection in authenticated images. Our scheme allows anyone to extract sub-image blocks from an original image (authenticated by the image producer) and generate a proof tag to prove the credibility of the extracted image blocks. The process of proof tag generation does not require any interaction with the image producer. In addition, the image producer is able to define must-be-preserved image blocks (e.g. producer logo) during the extraction. We define the security property for the authenticated sub-images and give a generic design with two core primitives: an ordinary digital signature scheme and a cryptographic accumulator. The security of our design can be reduced to the underlying cryptographic primitives and its practical performance is demonstrated by a bunch of evaluations. We believe the proposed design, together with other image authentication methods, will further facilitate image relevant services and applications.